2007
DOI: 10.1113/jphysiol.2006.126888
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of inhibition of rat recombinant heteromeric α1β glycine receptors by the low‐affinity antagonist SR‐95531

Abstract: The GABA A antagonist SR-95531 (gabazine) is known to block glycine receptors, albeit with low affinity. We have studied the effect of SR-95531 on rat recombinant α1β glycine receptors expressed in human embryonic kidney (HEK293) cells by recording macroscopic currents elicited by rapid glycine application to outside-out patches. SR-95531 has a fast unbinding rate (k offSR , about 3000 s −1 ) and this means that the time course of its unbinding is comparable to the expected time course of the transmitter in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…We tested for such saturation by measuring the degree of block of IPSCs by the low-affinity, competitive glycine receptor antagonist SR95531, under basal conditions and in pairs with 20 mM glycine in the presynaptic pipette. SR95531 blocks GABA A receptors with high affinity, although it also acts as a low-affinity competitive antagonist of glycine receptors at concentrations >30 μM (Beato et al, 2007; Beato, 2008). The off-rate of SR95531 from glycine receptors (~300 μs) is shorter than the duration of the synaptic glycine transient (Beato et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested for such saturation by measuring the degree of block of IPSCs by the low-affinity, competitive glycine receptor antagonist SR95531, under basal conditions and in pairs with 20 mM glycine in the presynaptic pipette. SR95531 blocks GABA A receptors with high affinity, although it also acts as a low-affinity competitive antagonist of glycine receptors at concentrations >30 μM (Beato et al, 2007; Beato, 2008). The off-rate of SR95531 from glycine receptors (~300 μs) is shorter than the duration of the synaptic glycine transient (Beato et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…SR95531 blocks GABA A receptors with high affinity, although it also acts as a low-affinity competitive antagonist of glycine receptors at concentrations >30 μM (Beato et al, 2007; Beato, 2008). The off-rate of SR95531 from glycine receptors (~300 μs) is shorter than the duration of the synaptic glycine transient (Beato et al, 2007). Thus, a significant fraction of glycine receptors will unbind SR95531 while glycine is still present in the synaptic cleft, making the degree of block by a set concentration of SR95531 inversely proportional to the amount of glycine released in the cleft following exocytosis (Beato, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…5B), we examined whether there was a presynaptic change in glycine release by taking advantage of SR95531, a low-affinity competitive antagonist of GlyRs (Wang and Slaughter, 2005;Beato et al, 2007). Inhibition of GlyRs by a competitive antagonist should be sensitive to changes in the amount of glycine released (Clements, 1996) because SR95531 has an estimated mean lifetime occupancy of 300 s and should unbind within the timescale of synaptic release (Beato et al, 2007).…”
Section: Chronic Glyt2 Inhibition Reduces Glycine Quantal Sizementioning
confidence: 99%
“…Inhibition of GlyRs by a competitive antagonist should be sensitive to changes in the amount of glycine released (Clements, 1996) because SR95531 has an estimated mean lifetime occupancy of 300 s and should unbind within the timescale of synaptic release (Beato et al, 2007). In outside-out or nucleated patches, SR95531 at 70 M, a concentration well below its binding equilibrium constant of 190 M (Beato et al, 2007), blocked the current evoked by 60 M glycine by 61 Ϯ 11% (n ϭ 3), whereas the current evoked by 200 M glycine was reduced only by 10.6 Ϯ 9.5% (data not shown). To mimic fast synaptic release, we recorded currents evoked by brief 1 ms iontophoretic applications of glycine and confirmed that the fraction of the current blocked by 70 M S95531 decreased as the amount of glycine release increased (Fig.…”
Section: Chronic Glyt2 Inhibition Reduces Glycine Quantal Sizementioning
confidence: 99%
See 1 more Smart Citation